Maternal singing and speech have beneficial effects on preterm infant’s general movements at term equivalent age and at 3 months: an RCT - Filippa, Manuela; Filippa, Gianluca; Della Casa, Elisa; Berardi, Alberto; Picciolini, Odoardo; Meloni, Sara Chiara; Lunardi, Clara; Cecchi, Alessandra; Sansavini, Alessandra; Corvaglia, Luigi; Grandjean, Didier, EVC Group; et al. (Frontiers in Psychology, 2025)
BackgroundGeneral Movements (GMs) are part of the spontaneous movement repertoire and assessing them helps to determine the integrity of the central nervous system in newborns. The aim of this study was to investigate the effects of maternal singing and speaking in the Neonatal Intensive Care Unit (NICU) on preterm infants’ GMs at term equivalent age and at 3 months.MethodsIn this multi-center randomized clinical trial, 56 stable preterm infants (25–32 weeks) were randomized to either an intervention group – in which mothers were asked to speak and sing to their infants for 20 min, 3 times per week, for 2 weeks – or to a control group. GMs were recorded both before and after the intervention – which took place at term equivalent age – and again at 3 months corrected age. The GMs were blindly coded based on the muted video tracks to produce both a general score and a detailed score.ResultsBefore the intervention, there were no significant differences between the two groups. The intervention wielded a significant effect on the GMs general score (p < 0.05). The effect was also marginally significant for the GMs detailed score (p = 0.06). To avoid influencing outcomes, future research should control for differences in maternal engagement outside of the intervention.ConclusionLive maternal singing and speaking are fundamental human practices that, in this study, enhanced preterm infants’ general movements and potentially supported their neurobehavioral development. Integrating and supporting early vocal interaction into routine NICU care is crucial for at-risk populations.